Effect of Chlamydomonas plastid terminal oxidase 1 expressed in tobacco on photosynthetic electron transfer. (21st January 2016) - Feilke, Kathleen; Streb, Peter; Cornic, Gabriel; Perreau, François; Kruk, Jerzy; Krieger‐Liszkay, Anja
Summary: The plastid terminal oxidase PTOX is a plastohydroquinone:oxygen oxidoreductase that is important for carotenoid biosynthesis and plastid development. Its role in photosynthesis is controversially discussed. Under a number of abiotic stress conditions, the protein level of PTOX increases. PTOX is thought to act as a safety valve under high light protecting the photosynthetic apparatus against photodamage. However, transformants with high PTOX level were reported to suffer from photoinhibition. To analyze the effect of PTOX on the photosynthetic electron transport, tobacco expressing PTOX‐1 from Chlamydomonas reinhardtii (Cr‐PTOX1) was studied by chlorophyll fluorescence, thermoluminescence, P700 absorption kinetics and CO2 assimilation. Cr‐PTOX1 was shown to compete very efficiently with the photosynthetic electron transport for PQH2 . High pressure liquid chromatography (HPLC) analysis confirmed that the PQ pool was highly oxidized in the transformant. Immunoblots showed that, in the wild‐type, PTOX was associated with the thylakoid membrane only at a relatively alkaline pH value while it was detached from the membrane at neutral pH. We present a model proposing that PTOX associates with the membrane and oxidizes PQH2 only when the oxidation of PQH2 by the cytochrome b 6 f complex is limiting forward electron transport due to a high proton gradient across the thylakoid membrane. Significance Statement: Plastid terminal oxidase is thought to act as a safety valve under stress, but paradoxically plants overexpressing PTOX suffer from oxidative stress. Here, using tobacco expressing PTOX1 from C. reinhardtii, we show that PTOX competes efficiently with photosynthetic electron flow but is inactive when the stroma is neutral. We therefore propose that membrane association of PTOX is controlled by the proton gradient.